Key Survival Factor, Mcl-1, Correlates with Sensitivity to Combined Bcl-2/Bcl-xL Blockade - Williams, Michelle M. (Mol Cancer Res, 2016)
An estimated 40,000 deaths will be attributed to breast cancer in 2016, underscoring the need for improved therapies. Evading cell death is a major hallmark of cancer, driving tumor progression and therapeutic resistance. To evade apoptosis, cancers use anti-apoptotic Bcl-2 proteins to bind to and neutralize apoptotic activators, such as Bim. Investigation of anti-apoptotic Bcl-2 family members in clinical breast cancer datasets, revealed greater expression and more frequent gene amplification of MCL1 as compared to BCL2 or BCL2L1 (Bcl-xL) across three major molecular breast cancer subtypes, Luminal (A and B), HER2-enriched, and Basal-like. While Mcl-1 protein expression was elevated in estrogen receptor α (ERα)-positive and ERα-negative tumors as compared to normal breast, Mcl-1 staining was higher in ERα+ tumors. Targeted Mcl-1 blockade using RNAi increased caspase-mediated cell death in ERα+ breast cancer cells, resulting in sustained growth inhibition. In contrast, combined blockade of Bcl-2 and Bcl-xL only transiently induced apoptosis, as cells rapidly acclimated through Mcl-1 upregulation and enhanced Mcl-1 activity, as measured in situ using Mcl-1/Bim proximity ligation assays. Importantly, MCL1 gene expression levels correlated inversely with sensitivity to pharmacological Bcl-2/Bcl-xL inhibition in luminal breast cancer cells, whereas no relationship was seen between gene expression of BCL2 or BCL2L1 and sensitivity to Bcl-2/Bcl-xL inhibition. These results demonstrate that breast cancers rapidly deploy Mcl-1 to promote cell survival, particularly when challenged with blockade of other Bcl-2 family members, warranting the continued development of Mcl-1 selective inhibitors for targeted tumor cell killing.